2022
DOI: 10.1007/s11831-022-09820-w
|View full text |Cite
|
Sign up to set email alerts
|

Point Cloud Generation for Meshfree Methods: An Overview

Abstract: Meshfree methods are becoming an increasingly popular alternative to mesh-based methods of numerical simulation. The biggest stated advantage of meshfree methods is the avoidance of generating a mesh on the computational domain. However, even today a surprisingly large amount of meshfree literature ironically uses the nodes of a mesh as the point set that discretizes the domain. On the other hand, already existing efficient meshfree methods to generate point clouds are apparently not very well known among mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 193 publications
0
9
0
Order By: Relevance
“…Nevertheless, due to the flexibility of mesh‐free schemes, the point cloud generation can be considerably easier than manual mesh generation. A detailed review of point generation methods can be found in Reference 27.…”
Section: Numerical Methodologiesmentioning
confidence: 99%
“…Nevertheless, due to the flexibility of mesh‐free schemes, the point cloud generation can be considerably easier than manual mesh generation. A detailed review of point generation methods can be found in Reference 27.…”
Section: Numerical Methodologiesmentioning
confidence: 99%
“…This is because inter-point distances are controlled to fixed multiples of h. The minimum distance between two points is controlled to be greater than r min h, and maximum hole size in the point cloud is given by r max h. This is enforced by merging particles that come too close, and adding them in holes where no points are present. For more details of these addition / deletion procedures, we refer to [15,51,57,59].…”
Section: Notationmentioning
confidence: 99%
“…The point clouds used in the present work are irregularly spaced, without any background grid or mesh. All points clouds are generated using an advancing front point generation method [57,54].…”
Section: Notationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible approach is to use randomlygenerated nodes [17,22]; this approach has been used (with some modifications) in areas such as compressive sensing [1] and function approximation in high dimensions [24]. Other approaches include iterative optimization [12,19,15], sphere-packing [16], QR factorization [34], and repulsion [9,35]. It is generally accepted that quasi-uniformly-spaced node sets improve the stability of meshless methods [36].…”
Section: Introductionmentioning
confidence: 99%